Wearable Electrochemical Biosensors for Advanced Healthcare Monitoring - Haowei Duan; Shuhua Peng; Shuai He; Shi‐Yang Tang; Keisuke Goda; Chun H. Wang; Ming Li (Advanced Science)
Abstract Recent advancements in wearable electrochemical biosensors have opened new avenues for on‐body and continuous detection of biomarkers, enabling personalized, real‐time, and preventive healthcare. While glucose monitoring has set a precedent for wearable biosensors, the field is rapidly expanding to include a wider range of analytes crucial for disease diagnosis, treatment, and management. In this review, recent key innovations are examined in the design and manufacturing underpinning these biosensing platforms including biorecognition elements, signal transduction methods, electrode and substrate materials, and fabrication techniques. The applications of these biosensors are then highlighted in detecting a variety of biochemical markers, such as small molecules, hormones, drugs, and macromolecules, in biofluids including interstitial fluid, sweat, wound exudate, saliva, and tears. Additionally, the review also covers recent advances in wearable electrochemical biosensing platforms, such as multi‐sensory integration, closed‐loop control, and power supply. Furthermore, the challenges associated with critical issues are discussed, such as biocompatibility, biofouling, and sensor degradation, and the opportunities in materials science, nanotechnology, and artificial intelligence to overcome these limitations.